O boicote no comportamento do consumidor - Cruz, Breno de Paula Andrade (2013)
This thesis introduces an issue which has not been very much explored in the area of consumers’ behavior: the boycott. The boycott has been analyzed in this research, as consumer leaving his behavior of buying in a company in reply to a context that not fits in his values or expectations. Thus, the investigation is divided into two researches. The first one analyzed the social networking environment in order to check whether this virtual world was appropriate for the understanding of the consumers’ behavior in relation to boycott. By the use of Netnography, the Non-Participating Observation and the Depth Interview in data collection, it has been seen that, besides the virtual environment contain relevant information about consumers’ boycott, another type of boycott, not discussed in the literature, was found following an empirical verification perspective: the relational boycott – an act of consumers’ repudiation emerges from a frustrated relationship or relationship attempt with a company. Study 1 therefore presents the contribution to the consumers’ boycott taxonomy in the literature. The second study makes use of factorial experiment (2x2x2) and the sample was 240 respondents to analyze the impact of three independent variables can be analyzed (Corporate Social Responsibility – CSR, Gender and Types of Goods – the normal or luxury ones) within the dependable variables Boycott Effectiveness (KLEIN; SMITH; JOHN, 2004) and the Intention to Boycott (BI). BEP (Boycott Effectiveness Perception) is a perception about the reflection of consumer over relation to the boycott as an individual strategy for a company changes its actions in decisions and strategies, and Boycott Intention (BI) is the final intention of consumer in relation to the boycott. Six hypotheses are presented and the results shows that Social Corporate Responsibility impacts either (BEP) Boycott Effectiveness Perception as interaction in boycotting (BI) which Gender is not ecstatically significant in BEP and BI; and that Type of Good Impacts (GI), but does not impact BEP. This thesis shows that on both studies there are insights for behavior consumer area and gaps which still need to be analyzed by other researchers who are in interested in the issue.